Percutaneous Ethanol Ablation of Hepatocellular Carcinoma: Periprocedural Onset Alcohol Toxicity and Pancreatitis Following Conventional Percutaneous Ethanol Ablation Treatment. (2009) - Burton, Kirsteen Rennie; O'Dwyer, Helena; Scudamore, Charles
Abstract : A novel case of acute pancreatitis in a patient treated with percutaneous ethanol injection (PEI) ablation for hepatocellular carcinoma is described. The most commonly reported adverse effects of PEI are hepatic or peritoneal hemorrhage, hepatic insufficiency or infarction. There are no previous reports of fatal acute pancreatitis as a result of conventional PEI.